Toxicological and anti-inflammatory profile of Synadenium grantii Hook. f. in mice. (1st March 2021) - de Souza, Jade André; Patel, Yasmin Beatrisse Klein; Grockoski, Heloise Adeli; Nunes, Roberta; Ramos, Silvia Aparecida; Pastor, Maria Verônica Dávila; Stoeberl, Luis Carlos; Campos, Adriana; Cechinel Filho, Valdir; Santin, José Roberto; Quintão, Nara Lins Meira
Abstract: Ethnopharmacological relevance: Synadenium grantii Hook. f., popularly known as "janaúba" or "leiterinha", is used in the folk medicine to treat gastric disorders, some types of neoplasias and inflammatory diseases. Aim of the study: The aim of this study was to show the anti-inflammatory activity of the methanol extract obtained from S. grantii stems and also certify the safety of the extract performing toxicological analysis. Material and methods: The anti-inflammatory activity was investigated using carrageenan-induced inflammation in the subcutaneous tissue of male Swiss mice orally pre-treated with the S. grantii extract (1, 3 or 10 mg/kg). The leukocyte influx (optical microscopy) and secretion of chemical mediators (TNF, IL-6 and IL-1β, by enzyme-linked immunosorbent assay) were quantified in the inflamed exudate. The toxicity was investigated using the dose-fixed procedure (acute toxicity) and repeated dose 28-day (subacute toxicity) in mice orally treated with S. grantii extract. The open field and rota-rod test were used to evaluate possible interference of adverse effect of S. grantii on motor coordination, locomotor and exploratory activity. Results: The analysis of the inflammatory exudate of S. grantii -treated mice demonstrated reduction in the polymorphonuclear cells (PMN) migration to the inflamed tissue, as well as the reduction of the pro-inflammatory cytokines TNF and IL-1β. Furthermore, the acute and sub-acute toxicity studies did not show significant changes in body weight, general behaviour, biochemical parameters, organ weight and liver and kidney histopathological analysis. However, animals acutely treated with S. grantii presented reduction in the number of crosses in relation to the vehicle group, without significant difference in the number of elevations and latency time between the groups in rota-rod test. The obtained results allow to set the NOAEL (Non-observed-adverse-effect level) in 100 mg/kg for this specie of rodent. Conclusions: Together, the results herein obtained show that S. grantii extract presented anti-inflammatory activity by decreasing the influx of PMN to the inflamed tissue, as well as the cytokines TNF and IL-1β levels. In addition, S. grantii extract seemed not to present significant acute or subacute toxicity when administered to mice, demonstrating for the first time the safety of this extract, when orally administered. Graphical abstract: Image 1